Assessment on distribution and habitat use by galliformes in Trong Gewog, Royal Manas National Park, Bhutan - Kinley Drukpa (CNR, Lobesa Kinley Drukpa, 2022)
includes acknowledgement and abstract
Keywords: Thesis